Institutionalizing corporate social responsibility within corporate communications in the survey of the Indonesian organizations - Abdullah, Zulhamri; Abdul Aziz, Yuhanis; Tai, Lit Cheng (2012)
Purpose - The purpose of this paper is to develop empirical measures of Asian corporate social responsibility (CSR) based on a David's dual process model of CSR for Indonesian corporations. Design/methodology/approach - A pilot survey consisting of 40 respondents was conducted and correlation and multiple regressions were used to test the relationship between the constructs. An instrument to measure CSR practices mainly focusing on CSR relational, CSR ethical/moral, and CSR discretionary is developed to see greater impacts on corporate reputation, legitimacy and corporate culture. Findings - The findings show CSR antecedents have significantly formed through the formalization of corporate communication management in the Indonesian organizations. The result provides evidence that CSR initiatives have a direct impact on corporate reputation. Specifically, there is a positive correlation between independent variables - CSR morality, CSR discretionary, CSR relational, culture and legitimacy with corporate reputation. Practical implications - The study acknowledges the increase in CSR initiatives within existing corporate communication practices in Indonesian corporations in their quest to gain public legitimacy and corporate governance. Originality/value - The study contributes to the CSR literature by explicitly linking CSR to corporate reputation and corporate culture and by developing proposed model of CSR that can be used in exploring a critical dimension in management of corporate identity in an Asian country.